2020
DOI: 10.3390/antiox9030262
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Prevents Mitochondrial Impairment Induced by Isoproterenol in Isolated Rat Heart Mitochondria

Abstract: Mitochondria are considered to be a power station of the cell. It is known that they play a major role in both normal and pathological heart function. Alterations in mitochondrial bioenergetics are one of the main causes of the origin and progression of heart failure since they have an inhibitory effect on the activity of respiratory complexes in the inner mitochondrial membrane. Astaxanthin (AST) is a xanthophyll carotenoid of mainly marine origin. It has both lipophilic and hydrophilic properties and may pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…One promising agent, an antioxidant called astaxanthin (AST), appears to have cardiovascular disease-related health benefits as shown in animal studies, as well as potential in the prevention and therapy of other pathological conditions associated with oxidative damage and mitochondrial dysfunction. AST treatment was found to improve the resistance of rat heart mitochondria to Ca 2+ -dependent stress, as well as decrease levels of CypD and increase levels of ADT in mitochondria in a model of experimental myocardial injury induced by isoproterenol [47,48].…”
Section: Discussionmentioning
confidence: 95%
“…One promising agent, an antioxidant called astaxanthin (AST), appears to have cardiovascular disease-related health benefits as shown in animal studies, as well as potential in the prevention and therapy of other pathological conditions associated with oxidative damage and mitochondrial dysfunction. AST treatment was found to improve the resistance of rat heart mitochondria to Ca 2+ -dependent stress, as well as decrease levels of CypD and increase levels of ADT in mitochondria in a model of experimental myocardial injury induced by isoproterenol [47,48].…”
Section: Discussionmentioning
confidence: 95%
“…Earlier, we showed that AST enhances the activity of the respiratory chain complexes and increases the concentration of basic subunits of these complexes in intact RHM [ 33 ]. Here, we examined changes in the concentrations of the main subunits of the respiratory chain complexes in RHM isolated from each group of rats upon the opening/closing of the mPTP ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, we showed that the pretreatment of rats with AST improves the functional state of the mitochondria by increasing the RCI and activity of respiratory chain complexes and ATP synthase in RHM injured by ISO [ 33 ]. Here, we used the same concentration of ISO and found that ISO injection decreased the RCI in RHM, whereas AST abolished the effect of ISO and increased the RCI in RHM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations